2002
DOI: 10.1007/s00109-002-0384-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein lipase: structure, function, regulation, and role in disease

Abstract: Lipoprotein lipase (LPL) catalyses the hydrolysis of the triacylglycerol component of circulating chylomicrons and very low density lipoproteins, thereby providing non-esterified fatty acids and 2-monoacylglycerol for tissue utilisation. Research carried out over the past two decades have not only established a central role for LPL in the overall lipid metabolism and transport but have also identified additional, non-catalytic functions of the enzyme. Furthermore, abnormalities in LPL function have been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
564
1
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 758 publications
(592 citation statements)
references
References 190 publications
15
564
1
12
Order By: Relevance
“…Insulin is known to exert a direct regulatory effect on HL and LPL. 107,108 Interestingly, only a few studies 6,52,56 adjusted for the effect of insulin. Mudali et al 6 showed that adjustments for insulin, BMI and other covariates did not significantly influence associations of SHBG with HDL-C and triglycerides.…”
Section: Lipid Profilementioning
confidence: 99%
“…Insulin is known to exert a direct regulatory effect on HL and LPL. 107,108 Interestingly, only a few studies 6,52,56 adjusted for the effect of insulin. Mudali et al 6 showed that adjustments for insulin, BMI and other covariates did not significantly influence associations of SHBG with HDL-C and triglycerides.…”
Section: Lipid Profilementioning
confidence: 99%
“…8,13,16,17 LPL plays a crucial role in lipoprotein metabolism and transport by catalyzing the rate-limiting step in the hydrolysis of TG component of circulating chylomicrons (CM) and very low-density lipoproteins (VLDL). 18 Thus, it implies that LPL controls the distribution of free fatty acids (FFA) within the body. Accordingly, changes in the tissue specific expression pattern of LPL are expected to affect the initiation and development of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…However, Oscar et al (2006) has observed t h a t LPL activity is directly associated with VLDL. On the other hand, abnormalities in LPL function have been found t o be associated with obesity a n d increase in triglyceride concentrations (Mead et al, 2002). There is significant correlation between LPL activity in abdominal fat and fat pad weight in birds, it means that the abdominal fat pad depot in birds of the high VLDL line takes up lipoprotein-borne fatty acids at 6-8 times the rate of that in the low VLDL line (Griffin et al, 1987).…”
Section: Resultsmentioning
confidence: 99%